This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: x = 9 – y Substitute for x in equation 1 3(9y) – y = 727 3y – y = 727 4y = 7 (Add 27 to each side)4y = 20 (Divide each side by 4) y = 5 Substitute for y in equation 2 X + (5) = 9 X – 5 = 9 (Add 5 to each side) X = 4 Therefore, x = 4, and y = 5 (4,5)...
View
Full
Document
This note was uploaded on 02/27/2008 for the course MATH 116 taught by Professor Philip during the Spring '08 term at A.T. Still University.
 Spring '08
 Philip
 Algebra

Click to edit the document details